Perencanaan Perbaikan Tanah dengan Menggunakan PVD (Prefabricated Vertical Drain) dan Timbunan (Preloading) pada Pembangunan Gedung ITS Tower 3 - Kurniawan, Agista Tri; Imananto, Eding Iskak; Yudianto, Eri Andrian (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2025)
The construction of ITS Tower 3 in Surabaya faces challenges due to the presence of soft clay soil characterized by low bearing capacity, high compressibility, and low permeability, which pose risks of significant settlement and endanger the stability of high-rise structures. To address this issue, soil improvement was planned using the preloading method combined with Prefabricated Vertical Drain (PVD) installation to accelerate the consolidation process. This study aims to analyze the magnitude of soil settlement and consolidation time under untreated conditions and compare them with conditions after applying PVD with different installation patterns (triangular and square) and spacing variations (1.0 m–1.6 m). The research methods include analyzing field and laboratory soil test data, calculating consolidation parameters, and simulating consolidation time based on different PVD configurations. The results show that PVD application significantly accelerates consolidation time compared to untreated soil, with triangular patterns at closer spacing providing higher efficiency despite requiring higher costs. Furthermore, the combination of preloading and PVD proved effective in accelerating initial settlement before structural construction, thereby reducing the risk of long-term deformation.